Pengaruh islamic corporate governance dan CSR terhadap tax avoidance dengan audit quality sebagai variabel moderasi - M. G. Wibawan; Wira A. Putra; Uun Sunarsih (Jurnal Akuntansi dan Manajemen, 2026)
The present study investigates the effects of Islamic Corporate Governance (ICG) and Corporate Social Responsibility (CSR) on tax avoidance, with Audit quality serving as a moderating variable. A quantitative methodology was applied, utilizing panel data regression analysis. Data were sourced from the annual financial statements of companies listed on the Indonesia Sharia Stock Index (ISSI) for the period 2021 to 2024. A purposive sampling technique was employed, resulting in a sample of 35 companies. Data analysis was performed using E-Views version 13. The findings demonstrate that ICG and CSR exert a significant influence on tax avoidance. Additionally, Audit quality moderates the relationship between ICG, CSR, and tax avoidance. These results underscore the critical role of Islamic Corporate Governance, Corporate Social Responsibility, and audit quality in shaping tax avoidance practices among Sharia-compliant companies.